Kompatibilitas Vegetatif Fusarium oxysporum dari Beberapa Tanaman Inang - Sri Sri Hartati; Ummu Salamah Rustiani; Lindung Tri Puspasari; Wawan Kurniawan (Agrikultura, 2016)
ABSTRACTVegetatif compatibility of Fusarium oxysporum on various hostsMany strains or race of Fusarium oxysporum can be grouped based on compatibility reproduction from a variety of different strains called Vegetative Compatibility Group (VCG). This study was aimed to determine how the grouping of several isolates of F. oxysporum and grouping of several hosts of the fungus by vegetative compatibility group. Fusarium oxysporum isolated from chickpea plants that showed symptoms of fusarium wilt. The isolates of F. oxysporum of chili and tomatoes obtained from the culture collections of Mycology Laboratory of IPB. Stages of vegetative compatibility testing assayed through recovery of nit mutants, the identification of phenotype of nit mutant, and complementation test. There are 29 mutants isolated from the isolates of F. oxysporum. Nit1 mutant was obtained from all isolates of beans, tomatoes and peppers. NitM and Nit3 mutant isolates were obtained from chickpea 4 and chili sequentially. Two VCG and one single self compatibility (SSC) were assayed from isolates of F. oxysporum based on complementation testing.Keywords: Beans, Fusarium wilt, Nit mutant, SSC, VCGABSTRAKJamur Fusarium oxysporum memiliki banyak forma spesialis dan ras. Jamur ini dapat dikelompokkan berdasarkan kompatibilitas reproduksi dari berbagai strain yang berbeda disebut dengan vegetative compatibility group (VCG). Penelitian ini bertujuan untuk mengetahui cara pengelompokkan F. oxysporum dan pengelompokkan jamur tersebut dari beberapa inang berdasarkan kelompok kompatibilitas vegetatifnya. Isolasi F. oxysporum dilakukan dari tanaman kacang panjang yang menunjukkan gejala layu fusarium. Isolat F. oxysporum dari cabai dan tomat berasal dari koleksi Laboratorium Mikologi IPB. Tahapan pengujian kompatibilitas vegetatif melalui pembiakan nit mutan, identifikasi fenotipe nit mutan, dan pengujian komplementasi. Isolasi mutan F. oxysporum didapatkan 29 mutan. Mutan nit1 didapatkan dari semua isolat yang diperoleh dari semua inang yang berbeda yaitu kacang panjang, tomat dan cabai. Mutan nitM hanya didapatkan dari isolat kacang panjang 4 dan mutan nit3 hanya didapatkan dari isolat cabai. Berdasarkan uji komplementasi F. oxysporum yang diuji terdiri dari dua VCG dan satu single self compatibility (SSC).Kata Kunci: Kacang panjang, Layu fusarium, Nit mutant, SSC, VCG